To find the point-slope form of the equation of the line that passes through the points (3, 34) and (10, 62), we first need to find the slope (m) of the line using the formula:
\[ m = \frac{y_2 - y_1}{x_2 - x_1} \]
Substituting in our points (3, 34) as \((x_1, y_1)\) and (10, 62) as \((x_2, y_2)\):
\[ m = \frac{62 - 34}{10 - 3} = \frac{28}{7} = 4 \]
Now we can use the point-slope form of a line, which is given by:
\[ y - y_1 = m(x - x_1) \]
Using the point (3, 34):
\[ y - 34 = 4(x - 3) \]
Thus, the correct point-slope equation is:
\[(y - 34) = 4(x - 3)\]
So the answer is:
(y - 34) = 4 (x - 3)